On The Issue of the Formation of Aesthetic Culture among Students of Primary Education in the Process of Teaching the Russian Language - Sobirzjanovna, Dustova Dildora; Madina, Latifova (European Journal of Life Safety and Stability (2660-9630), 2021)
This article reveals some aspects of the formation of the esthetic culture of students in the process of teaching the Russian language, analyzes the features of the upbringing of the esthetic culture of future teachers of primary education.